Al-Mg alloy negative electrode current collector, preparation method thereof and negative-electrode-free sodium metal battery
Al-Mg alloy negative electrode current collector was prepared by forming a magnesium plating layer on the surface of the aluminum foil and calcining treatment. The problems of high reactivity and instability of sodium metal negative electrodes in applications were solved, and uniform sodium deposition and improved battery cycle life were achieved.
Patent Information
- Application Number
- CN202411792160.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-21
AI Technical Summary
In practical applications, sodium metal negative electrodes face high reactivity and easy reaction with electrolyte to form unstable SEI films, resulting in uneven sodium deposition, dendrite growth, degradation of battery performance and safety hazards.
Magnetic sputtering technology is used to form a magnesium coating on the surface of the aluminum foil, and an Al-Mg alloy negative electrode current collector is prepared after calcination. It has a high sodium philtrum and stable three-dimensional structure, and is used in an anode-free sodium metal battery.
Induce uniform deposition of sodium, inhibit the growth of sodium dendrites, reduce active sodium loss, improve the cycle life of the battery, and improve the service life of the negative electrode current collector.
Smart Images

Figure CN119663205A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to an Al-Mg alloy negative electrode current collector and a preparation method thereof, and a negative electrode-free sodium metal battery. Background Art
[0002] Lithium-ion batteries have become an indispensable energy storage device in fields such as electric vehicles and portable electronic devices due to their high operating voltage, excellent rate performance, long cycle life, and no memory effect. However, with the uneven distribution of lithium resources and the continuous rise in prices around the world, the application of lithium-ion batteries in large-scale energy storage has been severely restricted. In this context, sodium-ion batteries, with their low cost and good cycle stability, have received extensive attention and research as a powerful supplement to lithium-ion batteries.
[0003] Although sodium-ion batteries have excellent performance in cost-effectiveness and cycle stability, the traditional sodium-ion battery negative electrode materials have low theoretical energy density and are difficult to meet the urgent demand for high energy density in the next generation of energy storage systems. Therefore, sodium metal batteries that directly use sodium metal as the negative electrode have emerged. With the advantages of high energy density, low reduction potential and low cost, they are regarded as one of the ideal candidates for the next generation of energy storage devices.
[0004] However, sodium metal anodes face many challenges in practical applications. Sodium metal has high reactivity and easily reacts with the electrolyte to form an unstable solid electrolyte interface (SEI) film. This unstable SEI film not only leads to uneven deposition of sodium and the formation of dendrites, but also aggravates the rupture of the SEI film and the consumption of the electrolyte, thereby reducing the coulombic efficiency of the battery. More seriously, the continued growth of sodium dendrites may cause safety hazards such as battery volume expansion, short circuit and even fire.
[0005] In order to meet these challenges, researchers have conducted a lot of modification research on sodium metal anodes in recent years, aiming to improve their stability and safety. These modification methods include using solid electrolytes, constructing artificial interface membranes, and modifying current collectors. Among them, the modification of the current collector of the sodium metal anode can effectively reduce the local current density, induce uniform sodium deposition, improve the deposition / stripping efficiency of sodium metal, and is expected to realize anode-free sodium metal batteries.
[0006] In a negative electrode-free sodium metal battery, the positive electrode material provides the only active sodium source, while the negative electrode directly uses a bare current collector without the need to deposit sodium metal on the current collector in advance. During the first charge process, sodium ions are released from the positive electrode material and deposited on the negative electrode current collector, forming a "real sodium metal negative electrode". During the subsequent battery discharge process, the active sodium on the negative electrode current collector is re-embedded into the positive electrode material, thereby achieving a charge and discharge cycle.
[0007] Aluminum is considered to be one of the excellent current collectors for sodium metal anodes because it does not react with sodium to form alloys and has significant cost advantages. However, there is a problem of uneven local current density distribution on the surface of commercial aluminum foil, which easily leads to the growth of sodium dendrites and the decline of battery performance. Summary of the invention
[0008] The purpose of the present application is to provide an Al-Mg alloy negative electrode current collector and a preparation method thereof and a negative electrode-free sodium metal battery to solve the above problems.
[0009] To achieve the above objectives, this application adopts the following technical solutions:
[0010] A method for preparing an Al-Mg alloy negative electrode current collector, comprising:
[0011] Magnesium is sputtered onto the surface of the aluminum foil by magnetron sputtering to form a magnesium coating on the aluminum foil;
[0012] The aluminum foil with the magnesium coating is calcined to obtain an Al-Mg alloy negative electrode current collector, wherein the Al-Mg alloy negative electrode current collector comprises an aluminum base layer and an Al-Mg alloy layer located on the aluminum base layer.
[0013] According to an embodiment of the present application, the thickness of the aluminum foil is 8-50 μm;
[0014] And / or, the target-substrate distance of the magnetron sputtering is 50-70 mm.
[0015] According to an embodiment of the present application, the vacuum degree of the magnetron sputtering is 1 x 10 -2 -1.5x 10 -2 Pa.
[0016] According to an embodiment of the present application, the Mg target power of the magnetron sputtering is 50-100W.
[0017] According to an embodiment of the present application, the working pressure of the magnetron sputtering is 1-3Pa.
[0018] According to an embodiment of the present application, the sputtering time of the magnetron sputtering is 5-12 minutes.
[0019] According to an embodiment of the present application, the calcination is carried out in an argon atmosphere, and the heating rate of the calcination is 2-8° C. / min.
[0020] According to an embodiment of the present application, the calcination temperature is 600-650°C;
[0021] And / or, the calcination time is 5-8h.
[0022] The present application also provides an Al-Mg alloy negative electrode current collector, which is prepared by the preparation method described above.
[0023] The present application also provides a negative electrode-free sodium metal battery, comprising an Al-Mg alloy negative electrode current collector prepared by the preparation method described above or comprising the Al-Mg alloy negative electrode current collector described above.
[0024] Compared with the prior art, the beneficial effects of this application include:
[0025] The present application introduces an Al-Mg alloy with high sodium affinity and stable three-dimensional structure into the negative electrode current collector, which can induce uniform sodium deposition, inhibit sodium dendrite growth, reduce active sodium loss, and improve the cycle life of the battery. The negative electrode current collector of the present application can be used in a negative electrode-free sodium metal battery. Moreover, the present application also has the advantages of simple operation and low raw material cost, which is conducive to large-scale promotion and application.
[0026] Specifically, the present application can grow a layer of three-dimensional Al-Mg alloy on the surface of the aluminum substrate layer as a negative electrode current collector. The aluminum substrate has excellent electrical conductivity, can quickly collect the current generated by the electrode, and transmit it efficiently. The Mg in the Al-Mg alloy, as a sodium-philic seed, can reduce the nucleation overpotential and induce uniform deposition of sodium, thereby improving the coulombic efficiency and cycle stability of the battery. In addition, the three-dimensional structure of the Al-Mg alloy can effectively increase the specific surface area of the current collector, reduce the local current density and sodium ion flux, increase the active nucleation sites, reduce dendrite deposition, and thus improve the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0028] Figure 1 This is a scanning electron microscope image of the Al-Mg alloy negative electrode current collector prepared in Example 1. DETAILED DESCRIPTION
[0029] As used herein:
[0030] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0031] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a sentence of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that sentence; other elements are not excluded from the claim as a whole.
[0032] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0033] In these examples, parts and percentages are by mass unless otherwise indicated.
[0034] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0035] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0036] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:
[0037] A method for preparing an Al-Mg alloy negative electrode current collector, comprising:
[0038] Magnesium is sputtered onto the surface of the aluminum foil by magnetron sputtering to form a magnesium coating on the aluminum foil;
[0039] The aluminum foil with the magnesium coating is calcined to obtain an Al-Mg alloy negative electrode current collector, wherein the Al-Mg alloy negative electrode current collector comprises an aluminum base layer and an Al-Mg alloy layer located on the aluminum base layer.
[0040] The Al-Mg alloy of the present application has high sodium affinity and a stable three-dimensional structure, which can induce uniform sodium deposition / stripping, inhibit sodium dendrite growth, and improve battery cycle life. Moreover, the substrate of the present application and the Al-Mg alloy interface are mutually integrated, which can improve the interface stability between the aluminum substrate and the Al-Mg alloy, and is conducive to improving the service life of the negative electrode current collector. The Al-Mg alloy negative electrode current collector prepared in the present application can be used in a negative electrode-free sodium metal battery.
[0041] According to some embodiments of the present application, before magnesium is sputtered onto the surface of the aluminum foil, the method further includes: pre-treating the aluminum foil. Pre-treating the aluminum foil includes: using deionized water, acetone, and anhydrous ethanol to perform ultrasonic cleaning three times alternately. Then, the aluminum foil is dried by infrared drying or vacuum drying. Pre-treating the aluminum foil can remove impurities and oil stains on the surface of the aluminum foil, thereby avoiding the problem of the magnesium coating not adhering firmly to the surface of the aluminum foil and falling off.
[0042] According to an embodiment of the present application, the thickness of the aluminum foil is 8-50 μm;
[0043] For example, the thickness of the aluminum foil may be 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, or any value between 8 and 50 μm.
[0044] And / or, the target-substrate distance of the magnetron sputtering is 50-70 mm. When the target-substrate distance is within the above range, the sputtered magnesium particles can maintain appropriate kinetic energy, can effectively diffuse on the aluminum foil, and can ensure that the particles are closely arranged, thereby generating a high-quality magnesium coating. If the target-substrate distance is too large, the kinetic energy of the sputtered magnesium particles reaching the surface of the aluminum foil substrate will be small, which is not conducive to the diffusion of particles on the substrate. If the target-substrate distance is too small, the kinetic energy of the sputtered particles is too large, and it is easy to migrate and diffuse on the substrate, which is not conducive to the formation of a dense film; and too high kinetic energy will also cause the particles to collide with the film, making the deposition thickness uneven.
[0045] For example, the target-substrate distance of magnetron sputtering can be 50 mm, 55 mm, 60 mm, 65 mm, 70 mm or any value between 50-70 mm.
[0046] According to an embodiment of the present application, the vacuum degree of the magnetron sputtering is 1 x 10 -2 -1.5x 10 -2 Pa.
[0047] For example, the vacuum degree of magnetron sputtering can be 1x 10 -2 Pa, 1.1x 10 -2 Pa, 1.2x 10 -2 Pa, 1.3x 10 - 2 Pa, 1.4x 10 -2 Pa, 1.5x 10 -2 Pa or 1x 10 -2 -1.5x 10 -2 Any value between Pa.
[0048] According to an embodiment of the present application, the Mg target power of the magnetron sputtering is 50-100W. When the Mg target power is within the above range, the Mg target can stably generate glow discharge, ensure the continuity and stability of the sputtering process, and maintain a suitable sputtering rate, which is conducive to forming a uniform and dense magnesium coating on the aluminum foil. If the Mg target power is too small, it will cause the glow discharge to be difficult to maintain and the film formation speed to be slow. If the Mg target power is too large, the sputtering rate will increase sharply, which will cause the sputtered particles to condense on the substrate. Nucleation is uneven, affecting the quality and performance of the magnesium coating.
[0049] For example, the Mg target power of magnetron sputtering can be 50W, 55W, 60W, 65W, 70W, 75W, 80W, 85W, 90W, 95W, 100W or any value between 50-100W.
[0050] According to an embodiment of the present application, the working pressure of the magnetron sputtering is 1-3Pa. Within the above working pressure range, it can ensure that an appropriate amount of gas atoms are ionized, thereby maintaining a stable sputtering process, and can also ensure that the deposition rate is moderate, which is conducive to the formation of a uniform and dense magnesium coating. The working pressure will affect the sputtering rate. If the working pressure is too low, the number of ionized gas atoms will be small, resulting in a lower deposition rate. The higher the working pressure, the higher the deposition rate. However, if the working pressure is too high, the sputtered target atoms will be scattered too much in the process of flying to the substrate, resulting in a decrease in the deposition rate.
[0051] For example, the working pressure of magnetron sputtering can be 1Pa, 2Pa, 3Pa or any value between 1-3Pa.
[0052] According to an embodiment of the present application, the sputtering time of the magnetron sputtering is 5-12 minutes. When the sputtering time is within the above range, the sputtering process can be fully carried out, the thickness and density of the magnesium coating can be guaranteed, and it is conducive to obtaining a magnesium coating with a uniform and smooth surface. If the sputtering time is too short, the quality of the film will be reduced, and if the sputtering time is too long, the uniformity of the film will be affected.
[0053] For example, the sputtering time of magnetron sputtering can be 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min or any value between 5 and 12 min.
[0054] According to an embodiment of the present application, the calcination is carried out in an argon atmosphere, and the heating rate of the calcination is 2-8°C / min. For example, the heating rate of the calcination can be 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min or any value between 2-8°C / min.
[0055] According to the embodiment of the present application, the calcination temperature is 600-650°C; within the above calcination temperature range, the mutual diffusion and reaction of Al and Mg elements can be effectively promoted to form a uniform alloy structure, and Al can be prevented from melting due to excessively high temperature. If the calcination temperature is too low, Al-Mg alloy cannot be formed, and if the calcination temperature is too high, it is easy to exceed the melting point of Al, causing the substrate to melt.
[0056] For example, the calcination temperature may be 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, or any value between 600-650°C.
[0057] And / or, the calcination time is 5-8 hours. For example, the calcination time can be 5 hours, 6 hours, 7 hours, 8 hours or any value between 5-8 hours.
[0058] The present application also provides an Al-Mg alloy negative electrode current collector, which is prepared by the preparation method described above.
[0059] The present application also provides a negative electrode-free sodium metal battery, comprising an Al-Mg alloy negative electrode current collector prepared by the preparation method described above or comprising the Al-Mg alloy negative electrode current collector described above.
[0060] According to some embodiments of the present application, the negative electrode-free sodium metal battery further includes a positive electrode, a negative electrode, an electrolyte and a separator.
[0061] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0062] Example 1
[0063] Embodiment 1 provides an Al-Mg alloy negative electrode current collector, and the preparation method thereof comprises:
[0064] The Al foil with a thickness of 8 μm was ultrasonically cleaned three times with deionized water, acetone, and anhydrous ethanol alternately, and then placed in the sputtering chamber. The chamber was evacuated to a vacuum degree of 1.5 x 10 -2 Pa, and then argon gas was introduced into the chamber to clean the surface of the deposited substrate. The target-substrate distance was set to 50 mm, the cathode Mg target sputtering power was 100 W, the working pressure was 2 Pa, and the sputtering time was 5 min. The substrate speed was set to 10 r / min. The sputtered Al substrate was transferred to a tubular furnace, and the Al-Mg alloy negative electrode current collector was prepared under the conditions of a heating rate of 2 ° C / min, a calcination temperature of 600 ° C, and a holding time of 5 h.
[0065] Figure 1 This is a scanning electron microscope image of the Al-Mg alloy negative electrode current collector prepared in Example 1. Figure 1 It can be seen that the Al-Mg alloy has a three-dimensional strip-like morphology of 0.2x 2μm, which increases the specific surface area of the substrate and provides more effective nucleation sites, which is beneficial to improving the wettability of the electrolyte, promoting uniform deposition of sodium, and inhibiting the growth of sodium dendrites.
[0066] Example 2
[0067] Embodiment 2 provides an Al-Mg alloy negative electrode current collector, and the preparation method thereof comprises:
[0068] The Al foil with a thickness of 20 μm was ultrasonically cleaned three times with deionized water, acetone, and anhydrous ethanol alternately, and then placed in the sputtering chamber. The chamber was evacuated to a vacuum degree of 1x 10 -2 Pa, and then argon gas was introduced into the chamber to clean the surface of the deposited substrate. The target-substrate distance was set to 70 mm, the cathode Mg target sputtering power was 50 W, the working pressure was 3 Pa, and the sputtering time was 12 min. The substrate speed was set to 10 r / min. The sputtered Al substrate was transferred to a tubular furnace, and the Al-Mg alloy negative electrode current collector was prepared under the conditions of a heating rate of 5 ° C / min, a calcination temperature of 650 ° C, and a holding time of 8 h.
[0069] Example 3
[0070] Embodiment 3 provides an Al-Mg alloy negative electrode current collector, and the preparation method thereof comprises:
[0071] The Al foil with a thickness of 50 μm was ultrasonically cleaned three times with deionized water, acetone, and anhydrous ethanol alternately, and then placed in the sputtering chamber. The chamber was evacuated to a vacuum degree of 1.2 x 10 -2Pa, and then argon gas was introduced into the chamber to clean the surface of the deposited substrate. The target-substrate distance was set to 60 mm, the cathode Mg target sputtering power was 80 W, the working pressure was 1 Pa, and the sputtering time was 10 min. The substrate speed was set to 10 r / min. The sputtered Al substrate was transferred to a tubular furnace, and the Al-Mg alloy negative electrode current collector was prepared under the conditions of a heating rate of 8 ° C / min, a calcination temperature of 620 ° C, and a holding time of 6 h.
[0072] Example 4
[0073] Embodiment 4 provides an Al-Mg alloy negative electrode current collector, and the preparation method thereof comprises:
[0074] The Al foil with a thickness of 30 μm was ultrasonically cleaned three times with deionized water, acetone, and anhydrous ethanol alternately, and then placed in the sputtering chamber. The chamber was evacuated to a vacuum degree of 1.2 x 10 -2 Pa, and then argon gas was introduced into the chamber to clean the surface of the deposited substrate. The target-substrate distance was set to 50 mm, the cathode Mg target sputtering power was 60 W, the working pressure was 3 Pa, and the sputtering time was 8 min. The substrate speed was set to 10 r / min. The sputtered Al substrate was transferred to a tubular furnace, and the Al-Mg alloy negative electrode current collector was prepared under the conditions of a heating rate of 6 ° C / min, a calcination temperature of 630 ° C, and a holding time of 7 h.
[0075] Comparative Example 1
[0076] A commercial aluminum foil with a thickness of 20 μm was used as the negative electrode current collector.
[0077] Comparative Example 2
[0078] The Al foil with a thickness of 20 μm was ultrasonically cleaned three times with deionized water, acetone, and anhydrous ethanol alternately, and then placed in the sputtering chamber. The chamber was evacuated to a vacuum degree of 1x 10 -2 Pa, and then argon gas was introduced into the chamber to clean the surface of the deposited substrate. The target-substrate distance was set to 70 mm, the cathode Mo target sputtering power was 50 W, the working pressure was 3 Pa, and the sputtering time was 12 min. The substrate speed was set to 10 r / min. The sputtered Al substrate was transferred to a tubular furnace, and the Al-Mo negative electrode current collector was prepared under the conditions of a heating rate of 5 ° C / min, a calcination temperature of 650 ° C, and a holding time of 8 h.
[0079] Comparative Example 3
[0080] The Al foil with a thickness of 20 μm was ultrasonically cleaned three times with deionized water, acetone, and anhydrous ethanol alternately, and then placed in the sputtering chamber. The chamber was evacuated to a vacuum degree of 1x 10 -2Pa, and then argon gas was introduced into the chamber to clean the surface of the deposited substrate. The target-substrate distance was set to 100 mm, the cathode Mg target sputtering power was 200 W, the working pressure was 5 Pa, and the sputtering time was 30 min. The substrate speed was set to 10 r / min. The sputtered Al substrate was transferred to a tubular furnace, and the Al-Mg alloy negative electrode current collector was prepared under the conditions of a heating rate of 5 ° C / min, a calcination temperature of 700 ° C, and a holding time of 4 h.
[0081] Performance test: In order to verify the performance of the current collectors of Examples 1-4 and Comparative Examples 1-3, the inventors used the current collectors of Examples 1-4 and Comparative Examples 1-3 to assemble a negative electrode-free sodium metal battery using the same method, and tested its electrochemical performance. Specifically, it includes:
[0082] The current collectors of Examples 1-4 and Comparative Examples 1-3 were cut into electrode sheets with a diameter of 12 mm respectively as negative electrode current collectors. When the battery was assembled, the Al-Mg alloy layer of the negative electrode current collector was facing the positive electrode. Sodium vanadium phosphate was used as the positive electrode, and 1 mol / L NaPF 6 / ethylene glycol dimethyl ether (DME) was used as the electrolyte and button cells were assembled in a glove box. The full cell was tested at a current density of 100 mA / g. The experimental results are shown in Table 1.
[0083] Table 1 Electrochemical performance test results of Examples 1-4 and Comparative Examples 1-3
[0084]
[0085]
[0086] It can be seen from Table 1 that the first coulombic efficiency of the full battery and the capacity retention rate after 100 cycles of Examples 1-4 are significantly better than those of Comparative Example 1, indicating that compared with commercial aluminum foil, the Al-Mg alloy negative electrode current collector prepared in Examples 1-4 can effectively improve the first coulombic efficiency and cycle stability of the battery.
[0087] In Comparative Example 2, the Mg target of Example 2 is replaced with a Mo target, and an Al-Mo negative electrode current collector is prepared in Comparative Example 2. The first coulombic efficiency of the full battery and the capacity retention rate after 100 cycles of Example 2 are significantly better than those of Comparative Example 2, indicating that compared with the Al-Mo alloy negative electrode current collector, the Al-Mg alloy negative electrode current collector can effectively improve the first coulombic efficiency and cycle stability of the battery.
[0088] The target-substrate distance, cathode Mg target sputtering power, working pressure, sputtering time, calcination temperature and holding time of Comparative Example 3 are different from those of Example 2. The first coulombic efficiency of the full battery and the capacity retention rate after 100 cycles of Example 2 are significantly better than those of Comparative Example 3, indicating that when the target-substrate distance, cathode Mg target sputtering power, working pressure, sputtering time, calcination temperature and holding time are within the range of this application, the Al-Mg alloy negative electrode current collector can have excellent electrochemical properties.
[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0090] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing an Al-Mg alloy negative electrode current collector, characterized in that: include: Magnesium is sputtered onto the surface of the aluminum foil by magnetron sputtering to form a magnesium coating on the aluminum foil; The aluminum foil with the magnesium coating is calcined to obtain an Al-Mg alloy negative electrode current collector, wherein the Al-Mg alloy negative electrode current collector comprises an aluminum base layer and an Al-Mg alloy layer located on the aluminum base layer.
2. The method for preparing the Al-Mg alloy negative electrode current collector according to claim 1, characterized in that: The thickness of the aluminum foil is 8-50 μm; And / or, the target-substrate distance of the magnetron sputtering is 50-70 mm.
3. The method for preparing the Al-Mg alloy negative electrode current collector according to claim 1, characterized in that: The vacuum degree of the magnetron sputtering is 1x 10 -2 -1.5x 10 -2 Pa.
4. The method for preparing the Al-Mg alloy negative electrode current collector according to claim 1, characterized in that: The Mg target power of the magnetron sputtering is 50-100W.
5. The method for preparing the Al-Mg alloy negative electrode current collector according to claim 1, characterized in that: The working pressure of the magnetron sputtering is 1-3Pa.
6. The method for preparing the Al-Mg alloy negative electrode current collector according to claim 1, characterized in that: The sputtering time of the magnetron sputtering is 5-12 minutes.
7. The method for preparing an Al-Mg alloy negative electrode current collector according to claim 1, characterized in that: The calcination is carried out in an argon atmosphere, and the heating rate of the calcination is 2-8° C. / min.
8. The method for preparing an Al-Mg alloy negative electrode current collector according to any one of claims 1 to 7, characterized in that: The calcination temperature is 600-650°C; And / or, the calcination time is 5-8h.
9. An Al-Mg alloy negative electrode current collector, characterized in that: The Al-Mg alloy negative electrode current collector is prepared by the preparation method according to any one of claims 1 to 8.
10. A negative electrode-free sodium metal battery, characterized in that: An Al-Mg alloy negative electrode current collector prepared by the preparation method according to any one of claims 1 to 8 or an Al-Mg alloy negative electrode current collector according to claim 9.
Citation Information
Cited By
Battery current collector, preparation method of battery current collector, negative-electrode-free sodium ion battery and preparation method of negative-electrode-free sodium ion battery
CN119905600A
Battery current collector and preparation method, negative electrode-free sodium ion battery and preparation method
CN119905600B
Alloy electrode, zinc metal battery composite electrode and preparation method thereof, and zinc battery
CN120709268A
Negative plate of sodium metal battery without negative electrode and application of negative plate
CN120998930A
Preparation process and application of current collector of negative-electrode-free sodium-ion battery
CN121394417A